2016
DOI: 10.1007/s10549-016-4058-7
|View full text |Cite
|
Sign up to set email alerts
|

Almost 2% of Spanish breast cancer families are associated to germline pathogenic mutations in the ATM gene

Abstract: ATM mutation prevalence in Spanish population highlights the importance of considering ATM pathogenic variants linked to breast cancer susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
1
9
0
3
Order By: Relevance
“…This mutation was previously reported in an Ataxia-Telangiectasia family [17]. In addition, other cancer types in this family have been associated with ATM mutations such as thyroid [18], ovarian [16] and breast tumours [15].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This mutation was previously reported in an Ataxia-Telangiectasia family [17]. In addition, other cancer types in this family have been associated with ATM mutations such as thyroid [18], ovarian [16] and breast tumours [15].…”
Section: Discussionsupporting
confidence: 64%
“…ATM had been known to be linked to breast cancer predisposition in BRCA-negative families [14,15]. Furthermore, ATM mutations have been found in ovarian cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…With the aim to explore new approaches, we have performed WES in two BRCAX families that were compatible with the presence of a recessive high‐risk gene, however, we have not found any suitable candidate under this model. Interestingly, though, we found heterozygous deleterious variants in the already known moderate‐risk susceptibility gene ATM (Tavera‐Tapia et al, ) and in what we present as a novel candidate gene, RECQL5 .…”
Section: Introductionmentioning
confidence: 54%
“…Results showed that enrichment of multiple defects in DDR genes are related to BC predisposition in those high-risk families, opening the possibility of further studies. Tavera-Tapia et al [52] analyzed the exome of a non-BRCA Spanish family and found a novel germline ATM mutation (c.5441delT; p.Leu1814Trpfs*14). In the same study, the ATM gene was further analyzed in a cohort of 392 non-BRCA cancer families and showed 1.78% prevalence of mutations in non-BRCA familial BC/OC and a 1.94% frequency in BC, suggesting that testing of this gene in Spanish non-BRCA families should occur.…”
Section: Wes Approach In Familial Non-brca Breast/ovarian Cancermentioning
confidence: 99%